2005
DOI: 10.1515/cclm.2005.066
|View full text |Cite
|
Sign up to set email alerts
|

Fucosylation of serum glycoproteins in lung cancer patients

Abstract: Increased expression of sialyl Lewis X or A antigens on metastatic cancer cells leads to their selectin-mediated extravasation. Profound fucosylation of the serum microenvironment may be a factor that interrupts adhesion and influences the formation of metastases. In this study we quantitatively analyzed fucosylation of serum glycoproteins in small-cell and non-small-cell lung cancer patients. Fucosylation of four chosen glycoprotein bands was measured as the reactivity with Aleuria aurantia lectin on nitrocel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 9 publications
2
36
1
Order By: Relevance
“…groups. In harmony with this current study, Kossowska et al (2005) showed that fucosylated oligosaccharides are specific markers for inflammation and tumorigenesis and previous clinico-pathological studies of colorectal and lung cancer patients as well as experimental models of these cancer cells indicated that increase in fucosylated residues promote metastatic potential and indicate poor prognosis which explained its higher level in 16 and 18 weeks p.i groups.…”
Section: Discussionsupporting
confidence: 88%
“…groups. In harmony with this current study, Kossowska et al (2005) showed that fucosylated oligosaccharides are specific markers for inflammation and tumorigenesis and previous clinico-pathological studies of colorectal and lung cancer patients as well as experimental models of these cancer cells indicated that increase in fucosylated residues promote metastatic potential and indicate poor prognosis which explained its higher level in 16 and 18 weeks p.i groups.…”
Section: Discussionsupporting
confidence: 88%
“…30,[36][37][38][39][40] Over-expression of haptoglobin, and changes in the level of fucose and/or sialic acid residues, are common themes emerging from all these studies, but no cancer-specific glycoform of haptoglobin has been found to date. Our studies of prostate cancer haptoglobin have opened up 2 new avenues for investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in early pregnancy increasing expression of sialic acid linked α2-3 in the deciduas surrounding the implantation site have been shown to be associated with the implantation of the embryo in the uterus of pregnant rats and mice [25]. The α2-3 (but not α2-6) linked sialic acid glycoconjugates, further modified by α1-3 fucosylation (a Lewis x epitope) are essential ligands for E-, P-, and L-selectin binding in adhesive interactions [20,26,27]. Modifications in sialic acid expression have been shown to occur during development and differentiation of porcine tissues.…”
Section: Discussionmentioning
confidence: 99%